Behavior Of The Elderly In Preventing COVID-19 - Lilik Setiawan (Chakra Brahmanda Lentera Institute, 2022)
Background: The pandemic makes the elderly adapt to the behavior of implementing the protocol health. In this New Normal, many older adults still do not wear a mask, wash their hands or use hand sanitizer, and do not keep their distance. The purpose of the study was to determine the behavior of the elderly in preventing Covid-19 in Ngrejo Village Tanggunggunung District Tulungagung Regency. Methods: Descriptive research design, population 377 respondents and sample 38 respondents using purposive sampling technique, research instrument questionnaire sheet. The research was carried out on February 28 – March 26, 2022. Variable of Elderly Behavior in Covid-19 Prevention. Data was analyzed using the mean formula and interpreted quantitatively. Results: The results obtained from 38 respondents showed that most of the Majority (63%) have positive Covid-19 prevention behavior and almost half of the respondents (37%) have negative Covid-19 prevention behavior. Conclusion: Behavior in influenced by knowledge, attitude, and live together. Through this research, it is expected that respondents who have positive behavior to maintain health protocol hebavior, and respondents who have negative behavior to improve behavior according to recommendations from government regarding health protocols such as washing hands. Wearing masks, and keeping a distance